2020
DOI: 10.4314/ijbcs.v14i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Effet de l’inoculation mycorhizienne avec des souches des champignons mycorhiziens arbusculaires sur la croissance de <i>Mucuna pruriens</i> (L.) DC en condition contrôlée

Abstract: Au Burkina Faso, l’élevage occupe plus de 80% des ménages ruraux et constitue le troisième produit d’exportation après l’or et le coton. De type extensif, cet élevage est basé essentiellement sur l’exploitation des ressources naturelles. Ainsi, il doit s’adapter aux grandes variations saisonnières et interannuelles des ressources en biomasse végétale et en eau. Or les aléas climatiques, l’étendue et la qualité des pâturages, de même que les contraintes rendent l’activité pastorale souvent précaire. C’e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
3
3
0
1
Order By: Relevance
“…As a result, Yac 2 mix appears to be more effective in improving cowpea growth. These results corroborate those of Haro et al [17] who have shown the effectiveness of mycorrhizal symbiosis on improving the growth of Mucunapruriens. These authors also showed that this efficacy was linked to the mycorrhizal inoculum.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, Yac 2 mix appears to be more effective in improving cowpea growth. These results corroborate those of Haro et al [17] who have shown the effectiveness of mycorrhizal symbiosis on improving the growth of Mucunapruriens. These authors also showed that this efficacy was linked to the mycorrhizal inoculum.…”
Section: Discussionsupporting
confidence: 92%
“…Results showed that mycorrhizal and excised seedlings have the greatest collar root diameter than control ones and then those treated separately with mycorrhization or excision. Similar results are found by Haro et al (2020) by proving an increase of 170.51% on plant length of inoculated plants compared to non-inoculated ones.…”
Section: Discussion Discussion Discussionsupporting
confidence: 85%
“…These nutrients were depleted over time as the plants grew. Similar results were obtained by Haro et al [25]. These authors showed that mycorrhizal inoculation that was ineffective at the test start (the first 30 days after sowing) was very beneficial for Mucuna pruriens by improving its growth and production of shoot, root and total biomass at 60 days after sowing.…”
Section: Grow Parameters Evaluationsupporting
confidence: 85%